1995
DOI: 10.1002/hed.2880170111
|View full text |Cite
|
Sign up to set email alerts
|

DNA content in adenoid cystic carcinomas

Abstract: Our results indicate that DNA ploidy estimations, S-phase value, and histologic grading are prognostic factors in adenoid cystic carcinomas. These examinations should therefore be incorporated in the evaluation of patients with adenoid cystic carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
1
22
1
1
Order By: Relevance
“…Analyses of chromosomal ploidy have shown that most classic non-solid ACC show a low degree of aneuploidy, much less than other types of carcinomas, but, ACC with solid histology show increased aneuploidy [51,52]. Studies using CGH and aCGH show a correlation of the degree of genetic alterations (change in DNA copy number, chromosome number, genetic deletion) with the degree of solid growth pattern [39,41,42], consistent with the notion that ACCs with solid histology represent a later stage in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of chromosomal ploidy have shown that most classic non-solid ACC show a low degree of aneuploidy, much less than other types of carcinomas, but, ACC with solid histology show increased aneuploidy [51,52]. Studies using CGH and aCGH show a correlation of the degree of genetic alterations (change in DNA copy number, chromosome number, genetic deletion) with the degree of solid growth pattern [39,41,42], consistent with the notion that ACCs with solid histology represent a later stage in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…11 -14 Franzén et al 11 reported 51 patients treated at the National Hospital (Oslo, Norway) and observed that prognosis was adversely influenced by grade 3 histology ( p = .0001), DNA aneuploidy, and an S phase of 6% or greater ( p = .0044). Luna et al 14 reported a series of 26 patients with submandibular gland adenoid cystic carcinomas treated at The University of Texas M. D. Anderson Cancer Center (Houston, TX) and found that aneuploid tumors were associated with a higher likelihood of solid cytoarchitecture, lymph node metastases, and advanced stage.…”
mentioning
confidence: 99%
“…Franzén et al, 8,11 in two studies on adenoid cystic carcinoma, showed an association between tumor grade and DNA ploidy, and a similar conclusion was achieved by Hicks et al 40 in a series of 48 mucoepidermoid carcinomas. In our study, all the low grade carcinomas had a DNA diploid pattern.…”
Section: Discussionmentioning
confidence: 54%
“…2 Several new biomarkers with putative clinical relevance in the assessment of tumor behavior have been investigated recently including DNA flow cytometry, which allows a fast and automated estimation of ploidy status and cell proliferation of the neoplasms. Previous reports have suggested that DNA flow cytometric parameters may have prognostic utility in some histologic types of salivary gland carcinomas, [3][4][5][6][7][8][9][10][11] but the findings are not concordant among studies. [12][13][14][15][16] This in part may be related to the fact that cytometric analysis has been performed nearly exclusively in a retrospective manner using paraffin embedded material.…”
mentioning
confidence: 92%
See 1 more Smart Citation